House of Falconer : In the Lion's Den - Book 2 - Bradford, Barbara Taylor, 1933- (UK St. Martins Press, an imprint of St. HarperCollins Publisher, 2019)
"From New York Times bestselling author Barbara Taylor Bradford comes the highly anticipated second book in the House of Falconer saga. James Lionel Falconer has risen quickly from a mere shop worker to being the right-hand man of Henry Malvern, head of the most prestigious shipping company in London. With Malverns daughter Alexis running away to the country after a terrible tragedy and refusing to return, James ascent to head of the company seems inevitable. But even a charmed life like James is not without its setbacks. A terrible fire threatens to end his merchant career before its had a chance to truly begin. Mrs. Ward, James former paramour, has a secret that could change his life forever. And his distaste for Alexis Malvern is slowly growing into feelings of quite a different sort. Can James continue to be the master of his own fate, or will all of his charm, intelligence, and wit finally fail him when he has to enter the lions den? Spanning the years from 1889 to 1892, In the Lions Den is Barbara Taylor Bradford at her historical storytelling best"--
Keywords: Merchants -- Fiction; Businesspeople -- Fiction; Man-woman relationships -- Fiction; Secrecy -- Fiction; Family secrets -- Fiction; Social classes -- Fiction; Great Britain -- History -- Victoria, 1837-1901; Fiction; England -- Social life and customs -- 19th century; Fiction; Historical fiction; Historical fiction; Domestic fiction; Novels